Originality of C. Levi-Strauss’ Social Anthropology - Gendrolis, Edmundas (Problemos, 1995)
C. Levi-Strauss’s methodological principles of investigation of culture are discussed in the paper. Structural analysis is said to be aimed at the explication of the structures of unconscious collective mind, which in its turn determines the whole variety of actual culture. The author of the paper does agree with those who criticize non-universality of the method, nevertheless pointing out the fact of the wide use of the method in various fields of culture.